Ranchers' readiness to adopt GPS-based mobile application technology to brand and identify cattle - Baker, Chase, author; Abrams, Katie, advisor; Switzer, Jamie, committee member; Switzer, Ralph, committee member (Colorado State University. Libraries, 2014)
The longstanding process of cattle branding remains relatively unchanged since the origination of the technique. Meanwhile, society continues to adapt alongside the evolution and progression of technological advancements. The infiltration of technology into the realm of ranching and, specifically, branding seems to be inevitable, though the readiness of ranchers to accept the fusion of branding with technology remains to be fully understood. To achieve a better understanding of this level of readiness, a conceptualization for a mobile application used in conjunction with a GPS microchip was developed. An exploratory, qualitative study was conducted to examine the readiness level for ranchers to abandon conventional branding methods in favor of the proposed technological approach. A combination of theories and models--diffusion of innovations, technology acceptance model, non-adoption of innovations, and uses and gratifications--were used in tandem to formulate the research questions. Nine in-depth interviews with ranchers across the state of Colorado yielded a better understanding of the current level of readiness for adoption of such an innovation. An analysis of the phenomenon at hand produced results demonstrating that ranchers are not ready to abandon their current practices. A strong affinity for the ranching lifestyle and distrust in technological security heavily influenced the respondents' hesitancy to express a willingness to adopt. The study conclusion posits that an agricultural innovation such as this concept for branding must preserve as many aspects of tradition as possible and must be introduced to the ranching community on a trial basis, thus allowing the spread of adoption to take place organically.
Keywords: adoption; agriculture; GPS; journalism; mobile applications; ranching